2022
DOI: 10.21203/rs.3.rs-1156799/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lipases and carboxylesterases are involved in interspecific pheromone differences between two moth species

Abstract: Moth sex pheromones are a classical model for studying sexual selection. Females produce a species-specific pheromone blend that attracts males. Revealing the enzymes involved in the interspecific variation in blend composition is key for understanding the evolution of these sexual communication systems. The nature of the enzymes involved in the variation of acetate esters, which are prominent compounds in moth pheromone blends, remains unclear. We identified enzymes involved in acetate metabolism in two close… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 63 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…To determine expression levels of sex pheromone biosynthesis‐related genes, we conducted qPCR experiments with primers of the following genes: d11 , carboxylesterase 21 ( cxe21 , also known as HsTED ), a lipase ( lipX ) and another esterase ( est1 ). We chose these genes because previous QTL analysis, RNA‐Seq and CRISPR experiments have indicated that these genes play a role in the biosynthesis of sex pheromone compounds in heliothine moths (De Fouchier et al, 2022; Fruitet et al, 2022; Groot et al, 2009; Vogel et al, 2010). Since cxe21 , lipX and est1 have recently been identified as players in the synthesis and degradation of acetate esters (De Fouchier et al, 2022; Fruitet et al, 2022), we expected to find these genes expressed in tissues producing pheromone compounds.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine expression levels of sex pheromone biosynthesis‐related genes, we conducted qPCR experiments with primers of the following genes: d11 , carboxylesterase 21 ( cxe21 , also known as HsTED ), a lipase ( lipX ) and another esterase ( est1 ). We chose these genes because previous QTL analysis, RNA‐Seq and CRISPR experiments have indicated that these genes play a role in the biosynthesis of sex pheromone compounds in heliothine moths (De Fouchier et al, 2022; Fruitet et al, 2022; Groot et al, 2009; Vogel et al, 2010). Since cxe21 , lipX and est1 have recently been identified as players in the synthesis and degradation of acetate esters (De Fouchier et al, 2022; Fruitet et al, 2022), we expected to find these genes expressed in tissues producing pheromone compounds.…”
Section: Methodsmentioning
confidence: 99%
“…We chose these genes because previous QTL analysis, RNA‐Seq and CRISPR experiments have indicated that these genes play a role in the biosynthesis of sex pheromone compounds in heliothine moths (De Fouchier et al, 2022; Fruitet et al, 2022; Groot et al, 2009; Vogel et al, 2010). Since cxe21 , lipX and est1 have recently been identified as players in the synthesis and degradation of acetate esters (De Fouchier et al, 2022; Fruitet et al, 2022), we expected to find these genes expressed in tissues producing pheromone compounds. Primers for the target genes were designed using Primer 3 Web version (primer3_results.cgi release 4.1.0) (see Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation